2010
DOI: 10.1523/jneurosci.2378-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

CREB Binding Protein Is Required for Both Short-Term and Long-Term Memory Formation

Abstract: CREB binding protein (CBP) is a transcriptional coactivator with histone acetyltransferase activity. Our prior study suggested that CBP might be a key target of presenilins in the regulation of memory formation and neuronal survival. To elucidate the role of CBP in the adult brain, we generated conditional knock-out (cKO) mice in which CBP is completely inactivated in excitatory neurons of the postnatal forebrain. Histological analysis revealed normal neuronal morphology and absence of age-dependent neuronal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
131
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(149 citation statements)
references
References 49 publications
17
131
1
Order By: Relevance
“…p300 therefore may be expected to compensate for a lack of CBP. However, we observed no change in p300 in the region of CBP deletion ( Figure 1) and therefore, similarly to findings in other CBP mutant mice (Kasper et al, 2006;Chen et al, 2010), it does not appear that p300 is being upregulated to compensate for a loss of CBP.…”
Section: Generation Of Focal Homozygous Cbp Deletion Using Cbp Flox/fsupporting
confidence: 87%
See 1 more Smart Citation
“…p300 therefore may be expected to compensate for a lack of CBP. However, we observed no change in p300 in the region of CBP deletion ( Figure 1) and therefore, similarly to findings in other CBP mutant mice (Kasper et al, 2006;Chen et al, 2010), it does not appear that p300 is being upregulated to compensate for a loss of CBP.…”
Section: Generation Of Focal Homozygous Cbp Deletion Using Cbp Flox/fsupporting
confidence: 87%
“…To date, six different types of Cbp mutant mice have been generated to examine the role of CBP in memory (Oike et al, 1999;Bourtchouladze et al, 2003;Alarcon et al, 2004;Korzus et al, 2004;Wood et al, 2005Wood et al, , 2006Chen et al, 2010). However, none of these Cbp genetically modified mice were designed to target a single brain region and only one generated a complete knockout of CBP, as a homozygous knockout of Cbp results in embryonic lethality (Tanaka et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the effect of a partial or total loss of CBP function show the involvement of its HAT activity in LTP and LTM, and suggest that CBP is not required for the formation of short-term memory (STM) [47,[199][200][201][202]. Nevertheless, another study using a conditional model with complete CBP inactivation in excitatory neurons of the forebrain showed an impairment of both memory types [203]. However, more recent studies confirm CBP involvement in LTM.…”
Section: Transgenic Hat Animal Modelsmentioning
confidence: 99%
“…Interestingly, at least one wild-type allele of cbp was required to mediate the effects of HDAC inhibition on memory functions [215]. A supportive study demonstrated that HDACi were inefficient in a complete knock down of cbp [203]. Thus, simply inducing a histone hyperacetylated state with HDACi does not adequately replace HAT activation, at least in certain functions (i.e., memory formation), likely reflecting the other potential roles of HAT (e.g., CBP).…”
Section: Hat Activation Vs Hdac Inhibition As a Therapeutic Strategymentioning
confidence: 99%
“…A crucial role of CREB signalling in memory formation was found in both invertebrates and vertebrates [30]. Generally, decreased CREB activity was associated with learning impairments in healthy aged animals [31,32] and with cognitive deficits in animal models of neurodegenerative disorders [33][34][35]. Importantly, the level of phosphorylated CREB and the activity-induced increase in CREB phosphorylation is diminished in ageing [36,37], and this itself may influence the ageing process [38,39].…”
Section: Functional Histological and Molecular Changes In The Ageingmentioning
confidence: 99%